Indigenous Product of Emotion - Nazlina, Shaari; Suhaifa, Ab Wahab (Universiti Malaysia Sarawak (UNIMAS), 2010)
This paper introduces the general framework of levels of product experienced by the indigenous people. Four distinct components are discussed in observing indigenous products: products as mediators to interaction, enhancers of social interaction, relating to identity and objects of emotion. These are crucial process that involves the life context, engagement of the users with the product, experience that continually refers to product reliability, creating a pleasing experience and satisfaction can greatly influence the success of a product. The aim of this study is to examine the adaptability of an evaluation method using the visual images to evaluate the impression of an indigenous product design based on Kansei. Kansei approach was used to address the emotional side of the product used by the indigenous people that satisfy basic functionality, usability and safety. In the design context, Kansei emphasized the designer’s imagery skills: the power to produce a mental image and use this in the creative process. It is important to understand how indigenous people used their creativity in designing products as each product portrays different form and shapes that had specific preferences. The quantitative feature values for indigenous products are collected and the relation between Kansei words and the visual feature of indigenous products are analyzed. A cluster analysis was carried out in order to determine the exact groups of products that fit to the user’s needs. A number of clusters were emerged which are able to identify particular design features and its usability. This study also gives attention to the behaviors of users when they perceived the artifact and their preferences’ or cultural bases work to their feelings. Results show that specific design used by the indigenous people basically based on user’s environment, emotional values and the contexts of product used. The implications for the design are that emotion acts as an important component of indigenous artifact sense –making and determines how artifacts are interpreted. This creates an affective artifact in many aspects such as the product’s functions, characteristic, associated meanings on actual product use, and perceives pleasure.